2018
DOI: 10.4103/ijo.ijo_904_17
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral herpes simplex keratitis reactivation after lacrimal gland botulinum toxin injection

Abstract: Botulinum toxin A (BTA) injections into lacrimal gland are being used for refractory epiphora due to intractable lacrimal disorders with success rates reported from 18% to 86%. Most common side effects are transient ptosis and diplopia. We report a case of a 59-year-old female injected with 2.5 units of BTA injection in each lacrimal gland for functional epiphora. The patient had a history of herpes simplex viral keratitis that was quiescent for more than 2 years. After 3 weeks, she developed reactivation of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…HSV reactivation has also been linked to local, systemic, and topical steroid medications including the use of intravitreal triamcinolone injection[ 84 ]. Narang et al [ 85 ] further reported a case of reactivation of HSK after bilateral botulinum toxin injection to manage epiphora[ 85 ]. Ishimaru et al [ 86 ] reported that the HSV-1 virus replicated in host tissue partly due to proteasomal degradation of the Ras-GRF2 factor, while also demonstrating that this can be reversed by the proteasome inhibitor MG132[ 86 ].…”
Section: Understanding the Pathogenesis Of Herpes Simplex Keratitismentioning
confidence: 99%
“…HSV reactivation has also been linked to local, systemic, and topical steroid medications including the use of intravitreal triamcinolone injection[ 84 ]. Narang et al [ 85 ] further reported a case of reactivation of HSK after bilateral botulinum toxin injection to manage epiphora[ 85 ]. Ishimaru et al [ 86 ] reported that the HSV-1 virus replicated in host tissue partly due to proteasomal degradation of the Ras-GRF2 factor, while also demonstrating that this can be reversed by the proteasome inhibitor MG132[ 86 ].…”
Section: Understanding the Pathogenesis Of Herpes Simplex Keratitismentioning
confidence: 99%
“…Описаны случаи возникновения редких осложнений при применении ботулотоксина: острого приступа глаукомы с закрытием угла передней камеры после его введения, что связано с мидриазом, возникшим на фоне парасимпатического воздействия ботулотоксина на ресничный узел [53]; отслойки сетчатки в результате ее перфорации при инъекции [54]; двустороннего кератита при лечении гиперсекреторной функции слезной железы. Авторы рекомендуют проводить тщательный сбор анамнеза перед применением ботулотоксина [55].…”
Section: ботулотоксин в терапии и эстетической медицинеunclassified